THE EFFECTS OF AGRICULTURE CREDIT COOPERATIVES TO CAPITAL ASSOCIATION (ATATURK 'S PERIOD 1935-1938) (Third Sector Social Economic Review, 2017)
When the components of the Gross National Product of the Republic of Turkey are examined, agricultural production has a very important place especially in the first years of the Republic. At the time of the establishment of the Republic of Turkey, approximately 80% of the population were earning their life through small agricultural farms. In our work, the effects of the Agricultural Credit Cooperatives established in 1935 with the Law No. 2836 on the accumulation of capital of small family farms between 1935-1938 will be tried to be revealed.In the Introduction section of our work, we will try to summarize the point reached by the agricultural credit facility studies that started with the Homeland Funds of Mithat Pasha in the Ottoman Empire and the legacy left to the Republic of Turkey. In the first part, the arrangements made between 1923-1935 and the situation of Agricultural Credit Cooperatives will be briefly expained. In the last part of our work, the regulations made with the Agricultural Credit Cooperatives Law will be explained, applications and results will be tried to make conclusions about the effects of the Agricultural Credit Cooperatives on the capital accumulation in Turkey during the period mentioned above based on the values reached as of 1938.
Keywords: Agricultural Credit; Agriculture Credit Cooperative; Agricultural Credit Cooperative; Ziraat Bank; Capital; Farmer; Atatürk Period.